2015
DOI: 10.4209/aaqr.2015.09.0566
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Size-Fractionated Origins of Aerosols over a Remote Coastal Site in Southern Taiwan

Abstract: In spring 2013 air samples were collected from a coastal site in the sparsely populated far south-west of Taiwan and analysed for ambient gases, inorganic salts, carboxylates, and saccharides. Concentration of ambient gases was in the order SO 2 > HCl > HNO 3 > NH 3 > HNO 2 . Day-night variation in concentrations indicated that photochemical conversion of HNO 2 to HNO 3 occurs during the day. PM 2.5 (16.16 ± 5.30 µg m -3 ) accounted for 61.1% of PM 10 mass concentrations. The main inorganic salts were SO 4 2-,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
(100 reference statements)
0
3
0
Order By: Relevance
“…In contrast, saccharides from biological sources showed the highest level in April (the spring bloom season) on Jeju Island, and sucrose contributed to as high as 80% of the total saccharides [16]. Primary saccharides (sucrose, fructose, glucose) showed a unimodal distribution, with a dominant peak occurring in coarse-particles, while anhydrosaccharides were more likely to exist in fine particles [17]. Until now, studies on saccharides have mainly been focused on levoglucosan to evaluate the contribution of biomass burning on air pollution, but information related to the other saccharides, especially those from biological derivations, is still limited, and the characteristics of saccharides during periods of variable pollution levels are lacking.…”
Section: Introductionmentioning
confidence: 94%
“…In contrast, saccharides from biological sources showed the highest level in April (the spring bloom season) on Jeju Island, and sucrose contributed to as high as 80% of the total saccharides [16]. Primary saccharides (sucrose, fructose, glucose) showed a unimodal distribution, with a dominant peak occurring in coarse-particles, while anhydrosaccharides were more likely to exist in fine particles [17]. Until now, studies on saccharides have mainly been focused on levoglucosan to evaluate the contribution of biomass burning on air pollution, but information related to the other saccharides, especially those from biological derivations, is still limited, and the characteristics of saccharides during periods of variable pollution levels are lacking.…”
Section: Introductionmentioning
confidence: 94%
“…Lung et al (2002) indicated that total ionic species accounted for 46.4% and 44.6% of PM 2.5 mass on dust events and non-dust-event days, respectively in Taipei. Recently, at a remote site in southern Taiwan, the concentrations of main inorganic salts, SO 4 2-, NH 4 + , Na + , NO 3 -, and Cl -, were also found to be high accounting for 48.8 ± 27.4% of the PM 2.5 (Tsai et al, 2015). Secondary aerosols , NH 4 + and NO 3 -) contributed approximately 50% and 60% of PM 2.5 mass in spring and winter respectively; but were responsible about 40% by mass in summer at Tainan, Taiwan (Lu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Dicarboxylic acids and related polar compounds, including oxocarboxylic acids and α-dicarbonyls, are known to be ubiquitous in atmospheric aerosols and comprise a significant fraction of OAs (Kawamura and Yasui, 2005;Pavuluri et al, 2010;Tsai et al, 2015). They are directly released to the atmosphere from primary sources such as fossil fuel combustion and biomass burning (Kundu et al, 2010;Tsai et al, 2013;Cong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%